Prevalence of bovine subclinical mastitis and isolation of its major causes in Bishoftu Town, Ethiopia - Birhanu, Misrak (BMC Res Notes, 2017)
OBJECTIVE: A cross-sectional study was conducted from November 2015 to March 2016 to estimate the prevalence, to assess the risk factors and to isolate the major etiological agent of subclinical mastitis in Bishoftu town. The study was conducted on 262 cross breed lactating cows selected from 12 intensively managed dairy farms. California mastitis test (CMT) and bacteriological culture methods were used as diagnostic tools. RESULT: From 262 cows examined, 105 (40.1%) and from 1048 quarters examined, 170 (16.1%) were positive for sub-clinical mastitis using CMT. All CMT positive samples were cultured for etiological agent identification. From 170 samples cultured, 153 were positive for known subclinical mastitis pathogens. The dominant bacteria isolated were Staphylococcus species from these Staphylococcus aureus (44.9%) was the major one followed by Streptococcus spp. (25.3%) and other gram negative enteric bacteria, Escherichia coli (8.8%). Age, body condition score, milk yield, and number of parity were considered as potential risk factors; among these, age and number of parity have statistically significance association with the occurrence of subclinical mastitis (P < 0.05) both in the CMT and the bacteriological tests.